Social-economic situation of the evacuated population in Kazakhstan during the Great Patriotic war (Journal of history, 2019)
The Great Patriotic War led to mass evacuation of the civilian population to logistic areas. Kazakhstan became one of the largest centers of accommodation of the evacuated population, the industrial enterprises, the cultural and educational organizations. The difficulties and problems which faced as the evacuated population, and local population and republican authorities are analyzed in the article; questions, connected how the population reacted to evacuation and a military situation and as they interacted with evacuated are considered. Location, employment and adaptation of the evacuated population took place in extremely severe conditions of wartime. The leaders of the Kazakh SSR tried to control process of location and creation for the evacuated population of acceptable living conditions, fought against the heartless attitude towards their needs and applied severe measures of party collecting, however a lack of resources, material and human, did not give it to make in due to volume. The research is based on archival documents, normative legal acts of wartime.